A Village Community Empowerment Model for Waste Management to Enhance Community Entrepreneurial Intention - Burhanuddin Burhanuddin; Saiful Prayogi; Nova Kurnia; Muhali Muhali; Ika Nurani Dewi (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Waste management in rural areas continues to face several challenges, including low levels of household waste sorting, limited waste-processing facilities, and the underutilization of waste as an economic resource. This study aimed to analyze the improvement in rural community entrepreneurial intention after participating in a waste bank-based empowerment program. A mixed-methods approach with an explanatory sequential design was employed. The quantitative phase used a pre-experimental one-group pretest-posttest design without a control group, while the qualitative phase was conducted through semi-structured interviews. The participants consisted of 10 program participants from Senteluk Village, Batulayar District, West Lombok Regency, and one waste bank manager. The quantitative instrument was an entrepreneurial intention questionnaire based on the Theory of Planned Behavior, covering three dimensions: attitude toward behavior, subjective norms, and perceived behavioral control. Quantitative data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and a paired sample t-test, while qualitative data were analyzed thematically. The results showed that the mean entrepreneurial intention score increased from 15.30 in the pretest to 51.30 in the posttest, with a mean gain of 36.00. The paired sample t-test indicated a significant difference between pretest and posttest scores, t(9) = 29.50; p < 0.001. The qualitative findings revealed that the program encouraged a shift in participants’ perspectives on waste, strengthened social support, increased participants’ self-confidence, and fostered interest in waste-based enterprises, particularly organic fertilizer production. However, limitations related to equipment, capital, and market access still require attention. This study concludes that waste bank-based empowerment is associated with increased entrepreneurial intention among rural communities, although the sustainability of its impact requires further mentoring and the strengthening of the local business ecosystem.